SYSTEMATIC REVIEW: COMPARATIVE STUDY OF HOSPITALLINEN MANAGEMENT - Dewi, Nur Fadilah; Siregar, Jihan Luthfiyyah (Jurnal Vokasi Indonesia, 2021)
Healthcare-Associated Infections (HAIs) are disease complications that often occur in the provision of health services in the world. There are one million four hundred thousand infections each year due to HAIs. Responding to the high number of incidents, a solution is needed to reduce the number of HAIs. One of them is managing linen appropriately. However, a solution that was expected to be the key to suppressing the incidence of HAIs was found to be the plurality of problem. Various predecessor researchers discussed the diversity of problems and the complexity found at the stage of washing linen management. Even though the washing stage plays an important role in the success of linen management. On this basis, this journal also aims to compare the five precursors of research based on theoretical proper management of linen in order to enrich the treasury of the development of science, insight and as a reference for information in determining preventive measures for unexpected things. The research method used is a systematic literature review, then produces conclusions in the form of five hospitals that are examined based on the minimum requirements for hospital linen management guidelines that have met the requirements (>55%). However, after a comprehensive review, there are so many problems that are not included in the research variables. The plurality of problem was found at every process of linen management, linen management tools, tools and materials, linen quality and the behavior of linen management workers.